İlkokul 4. Sınıf Öğrencilerinin Bilinçli Tüketicilik Durumlarının İncelenmesi - Uyanık, Can (Muş Alparslan Üniversitesi, 2020)
The aim of this study was to examine elementary fourth graders'status of conscious consumerism. The present study was designed by adopting the mixed method approach. It was conducted with fourth graders from 15 elementary schools located in the Eskisehir. Quantitative data were gathered from 478 students through Conscious Consumerism Level Scale, and qualitative data from 15 students through semi-structured interviews. It was also found that the fourth grades’ levels of conscious consumerism significantly differed based on the socio-economic environment of the school parents’ education levels, monthly income of the family, parents’ professional state and state of saving their pocket-money. It was found that socio-economic environment was an effective variable on the students'conscious consumerism levels.

Bu araştırmanın amacı, ilkokul dördüncü sınıf öğrencilerinin bilinçli tüketicilik durumlarını incelemektir. Araştırma, karma yöntem yaklaşımıyla tasarlanmıştır. Araştırmanın uygulaması ilkokul Eskişehir’de bulunan 15 ilkokulun 4. sınıf öğrencileri ile gerçekleştirilmiştir. Araştırma kapsamında 478 öğrenciden Bilinçli Tüketicilik Düzeyi Ölçeği aracılığıyla nicel, 15 öğrenciden yarı yapılandırılmış görüşmeler yoluyla nitel veriler elde edilmiştir. Öğrencilerin bilinçli tüketicilik düzeylerinin okulun bulunduğu sosyoekonomik çevreye, annenin ve babanın eğitim düzeyine, ailenin aylık gelir düzeyine, annenin ve babanın mesleki durumuna ve öğrencilerin harçlıklarını biriktirme durumlarına göre anlamlı bir biçimde farklılaştığı sonucuna ulaşılmıştır. Sosyoekonomik çevrenin öğrencilerin bilinçli tüketicilik düzeyleri üzerinde etkili bir değişken olduğu belirlenmiştir.
Examining 4th Grade Primary School Students’ the Status of Conscious Consumerism
anemon
Keywords: Conscious Consumption; Primary School; Mixed Method; Consumer Socialization; İlkokul; Bilinçli tüketicilik; tüketici sosyalleşmesi; karma yöntem